2019
DOI: 10.1177/2331216519833567
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of the Inner Ear Function During and After Cochlear Implant Insertion Using Electrocochleography

Abstract: To preserve residual hearing during cochlear implant (CI) surgery, it is desirable to use intraoperative monitoring of inner ear function (cochlear monitoring), especially during electrode insertion. A promising method is electrocochleography (ECochG). Within this project, the relations between ongoing responses (ORs), recorded extra-and intracochlearly (EC and IC), and preservation of residual hearing were investigated. Before, during, and after insertion of hearing preservation electrodes, intraoperative ECo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(73 citation statements)
references
References 37 publications
3
68
1
1
Order By: Relevance
“…However, the clinical relevance of EcochG data for CI users has been reported in the literature according to a recent systematic review [ 37 ], which shows hearing preservation as an important and highly discussed topic. Correlation analyses between postoperative hearing thresholds and EcochG recordings have been reported in the literature [ 38 , 39 , 40 ] and were not part of this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical relevance of EcochG data for CI users has been reported in the literature according to a recent systematic review [ 37 ], which shows hearing preservation as an important and highly discussed topic. Correlation analyses between postoperative hearing thresholds and EcochG recordings have been reported in the literature [ 38 , 39 , 40 ] and were not part of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Five articles (5,9,(12)(13)(14) analyzed extracochlear ECochG recordings. Three articles are published by the same research group (5,9,13), including different subjects each time.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Three articles are published by the same research group (5,9,13), including different subjects each time. Adunka et al (12) included 31 and Haumann et al (14) 10 subjects. Both studies found no correlation between changes of extracochlear ECochG recordings and hearing threshold changes 4 weeks after surgery.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…The implementation of a tool like the CHD could bring other benefits. For example, the device could later on be combined with additional intraoperative measurements such as fluoroscopy [39], or cochlear monitoring [40] in order to achieve a deeper understanding of the electrode insertion process and the underlying mechanism of intracochlear trauma. Ultimately, more information and strategies could be gathered to develop different approaches that could guarantee preservation of residual hearing.…”
Section: Discussionmentioning
confidence: 99%